The role of the murine motor cortex in action duration and order - Yin, Henry H. (Frontiers in Integrative Neuroscience, 2009)
This study examined the contributions of the primary and secondary motor cortices (M1 and M2) to action differentiation and sequencing in mice. In Experiment 1, mice with excitotoxic lesions of M1 and M2 and sham controls learned to emit lever presses exceeding a criterion duration to earn food rewards. Duration differentiation obeys Weber’s law—i.e. the spread of the distribution is proportional to the average duration. M1 or M2 lesions did not affect differentiation of press durations. Experiment 2 studied the effects of the same lesions on the learning of a simple sequence consisting of two lever presses, one distal, and the other proximal, to the reward. M2 lesions impaired the acquisition and reversal of this sequence. M1 lesions, by contrast, had no effect on acquisition but impaired sequence reversal. Moreover, duration of the first press in a sequence was on average twice as long as that of the second press, though this ratio was not affected by motor cortex lesions. Together these results offer a first glimpse into the cortical substrates of instrumental differentiation in mice.